Rossy's Entertainment's Management Strategy in Improving Existence and Competitiveness - Desti Fitriyani; Syamsul Rizal; Wiwin Purwinarti (EDUJAVARE: International Journal of Educational Research, 2026)
The development of the creative industry in Indonesia in the last decade has shown very dynamic and multidimensional growth. This study aims to analyze the management strategies implemented by Rossy's Entertainment in maintaining its existence and competitiveness in Serang City. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. Informants included the studio founders, instructors, administrators, and active members. Data were analyzed using the interactive model of Miles, Huberman, and Saldana (2020), supported by source triangulation to ensure data validity. The findings reveal that Rossy's Entertainment applies systematic management strategies through program planning, structured organization, consistent training activities, and regular evaluations. To strengthen its existence, the studio actively utilizes social media, collaborates with government institutions, and participates in various regional and national art events. In terms of competitiveness, the studio emphasizes performance innovation, instructor quality, and member development. The study concludes that adaptive and sustainable management strategies play an important role in strengthening the existence and competitiveness of Rossy's Entertainment within the creative arts industry in Serang City.